Protein-Protein Interaction between Fli-1 and GATA-1 Mediates Synergistic Expression of Megakaryocyte-Specific Genes through Cooperative DNA Binding - Eisbacher, Michael (American Society for Microbiology, 2003)
Friend leukemia integration 1 (Fli-1) is a member of the Ets family of transcriptional activators that has been shown to be an important regulator during megakaryocytic differentiation. We undertook a two-hybrid screen of a K562 cDNA library to identify transcription factors that interacted with Fli-1 and were potential regulators of megakaryocyte development. Here we report the physical interaction of Fli-1 with GATA-1, a well-characterized, zinc finger transcription factor critical for both erythroid and megakaryocytic differentiation. We map the minimal domains required for the interaction and show that the zinc fingers of GATA-1 interact with the Ets domain of Fli-1. GATA-1 has previously been shown to interact with the Ets domain of the Fli-1-related protein PU.1, and the two proteins appear to inhibit each other's activity. In contrast, we demonstrate that GATA-1 and Fli-1 synergistically activate the megakaryocyte-specific promoters GPIX and GPIbα in transient transfections. Quantitative electrophoretic mobility shift assays using oligonucleotides derived from the GPIX promoter containing Ets and GATA binding motifs reveal that Fli-1 and GATA-1 exhibit cooperative DNA binding in which the binding of GATA-1 to DNA is increased approximately 26-fold in the presence of Fli-1 (from 4.2 to 0.16 nM), providing a mechanism for the observed transcriptional synergy. To test the effect on endogenous genes, we stably overexpressed Fli-1 in K562 cells, a line rich in GATA-1. Overexpression of Fli-1 induced the expression of the endogenous GPIX and GPIbα genes as measured by Northern blot and fluorescence-activated cell sorter analysis. This work suggests that Fli-1 and GATA-1 work together to activate the expression of genes associated with the terminal differentiation of megakaryocytes.